Study of the effects of climate warming on seed germination and seed longevity of snowbed species - Bernareggi, Giulietta (Università degli Studi di Parma. Dipartimento di Biologia evolutiva e funzionale, 2019)
Understanding how climate change will affect the distribution and the phenology of plants is becoming an increasingly important topic in ecological studies. In response to climate warming, there are documented upward shift and alterations of phenology and physiology of several plant species. Despite this, the effects of climate change on plant regeneration from seeds have largely been neglected. However, regeneration from seeds, a key event in the plant life cycle, could be significantly affected by climate warming. In this regard, we investigated how climatic changes will affect the seasonal dynamics of seed germination and seedling survival in two different alpine context. The first part refers to five species inhabiting a snowbed located at the Gavia pass (Parco Naturale dello Stelvio). Here, plants were exposed, in the field, to natural conditions and to artificial warming using Open Top Chambers proposed by the ITEX (International Tundra Experiment). The germination curves of seeds produced were compared in order to highlight differences in seed germination ecology and in seed physiology induced by the climate warming. In the second part, we considered two tree species that form the treeline in Davos (Switzerland). As a surrogate of climate warming we used the natural thermal gradient driven by the altitude and we compared the germination behavior of the species studied in three sites at three different elevations in order to evaluate the likelihood of treeline shift under the predicted climate warming.